The Marital Process in Chamchamal: An Anthropological Study (Raparin Journal of Humanities (RJH), 2025)
This study aims to analyze marriage ceremonies in Chamchamal township. The study highlights the social, cultural, and current changes in the ceremony. The importance of the study is shown by the fact that Chamchamal is a local community and wedding ceremonies and types have not been conducted an anthropological study according to the researchers. The purpose of this study; It sheds light on the marriage ceremony and identifies and presents the methods and types of marriage in Chamchamal. Also highlighting the changes that have happened to the ceremony today. The method used in this study is anthropological method. The researchers tried to understand the meaning, symbols and signs of how marriage is conducted in Chamchamal. (5) women and (6) men were used as samples to obtain information. To obtain more information, use was made of (participation and direct observation, documents, data and information, use of photography and audio recording and notebook record). The study concluded that ordinary marriage is the most common form in Chamchamal, while types such as wife-to-wife, adult-to-child and blood revenge existed only in the kind of old history of the region and are now gone. However, the form of wedding ceremonies has changed with social and cultural changes. The new generation of Chamchamal has been influenced by global and local changes. Unlike in the past, when parents played a major role in choosing a spouse, the majority of young people now choose their own spouses. Khanabandan still continues,and Pashtelana (weekly) ceremony has retained its importance, with special gifts or money being taken to the couple according to the means of the family.